Effect of Communication, Emotional Intelligence and Work Climate on Employee Performance at Mercure Sanur Resort Bali - I Komang Suryadnya Diputra; I Nyoman Mustika (Journal of International Conference Proceedings, 2022)
Competition in the accommodation service business is increasingly complex, in order to realize the company's success in achieving its goals. An indicator of success that must be considered in business implementation is the realization of high performance. This study aims to determine the effect of communication on employee performance, to determine the effect of emotional intelligence on employee performance, and to determine the effect of work climate on employee performance at Mercure Resort Sanur Bali. This research was conducted at Mercure Resort Sanur Bali. The background for choosing this location was because there were problems related to communication, emotional intelligence and work climate in an effort to improve employee performance at Mercure Resort Sanur Bali. The number of samples in this study were 70 respondents and the data analysis method used in this study was using multiple linear regression analysis techniques, coefficient of determination test, and statistical t test. with the analysis program, namely SPSS version 25.0 for windows. The results of the analysis show that partially and simultaneously Communication, Emotional Intelligence and Work Climate have a positive and significant effect on Employee Performance at Mercure Resort Sanur Bali.Â Keywords: Communication, Emotional Intelligence, Work Climate and Performance Employee.